2022
DOI: 10.3390/jof8080854
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Cell Wall Remodeling Genes Is Part of the Dynamic Phase-Specific Transcriptional Program of Conidial Germination of Trichoderma asperelloides

Abstract: The nature of saprophytic and mycoparasitic hyphal growth of Trichoderma spp. has been studied extensively, yet its initiation via conidial germination in this genus is less well understood. Using near-synchronous germinating cultures of Trichoderma asperelloides, we followed the morphological progression from dormant conidia to initial polar growth to germling formation and to evidence for first branching. We found that the stage-specific transcriptional profile of T. asperelloides is one of the most dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The authors’ analyses revealed new and important aspects of early fungal ingress in F. graminearum that can form the basis for improvement of antifungal strategies, including a comparative gene expression finding that toxisomes are not fully functional until after penetration of the host cells. Based on a study using near-synchronous germinating cultures of T. asperelloides (a strain used in biocontrol that was formerly identified as T. asperellum ), it has been reported that the transcript abundance of half of the annotated genome is reduced during early conidial germination ( Grotikov et al., 2022b ). In this study, it was also discovered that the expression of the chitin synthase and glucan elongase families is significantly increased during germination in the presence of a basidiomycete host, Rhizoctonia solani (Ceratobasidiaceae, Cantharellales), indicating that host recognition can occur during the early stages of mycoparasite development ( Grotikov et al., 2022b ).…”
Section: New Details and New Omics Data On The Sordariomycetes Contin...mentioning
confidence: 99%
“…The authors’ analyses revealed new and important aspects of early fungal ingress in F. graminearum that can form the basis for improvement of antifungal strategies, including a comparative gene expression finding that toxisomes are not fully functional until after penetration of the host cells. Based on a study using near-synchronous germinating cultures of T. asperelloides (a strain used in biocontrol that was formerly identified as T. asperellum ), it has been reported that the transcript abundance of half of the annotated genome is reduced during early conidial germination ( Grotikov et al., 2022b ). In this study, it was also discovered that the expression of the chitin synthase and glucan elongase families is significantly increased during germination in the presence of a basidiomycete host, Rhizoctonia solani (Ceratobasidiaceae, Cantharellales), indicating that host recognition can occur during the early stages of mycoparasite development ( Grotikov et al., 2022b ).…”
Section: New Details and New Omics Data On The Sordariomycetes Contin...mentioning
confidence: 99%
“…Chitinases are also present in morphogenesis, acting in cell growth and expansion of these fungi, as reported for the fungus Trichoderma asperelloides; its 17 chitinase genes are expressed during germination of the microorganism's conidia (GORTIKOV et al, 2022).…”
Section: Production Of Fungal Chitinasesmentioning
confidence: 77%
“…Its hydrophobic wall allows it to be transported by the wind while remaining dormant, until it finds an environment with enough nutrients to activate its metabolism [42]. From this moment on, the conidium starts so-called isotropic growth [43]. After approximately 6-8 h, it develops into a germ tube [44].…”
Section: Introductionmentioning
confidence: 99%